Community nutrition planning health promotion and disease prevention - Nnakwe, Nweze Eunice (Jones & Bartlett Learning, 2018)
"The third edition of Community Nutrition: Planning Health Promotion and Disease Prevention provides students and professionals with the knowledge, skills, tools, and evidence-based approaches they need to effectively promote health and prevent disease. Reflecting the latest direction in public health and community nutrition, it considers the comprehensive approach taken by practitioners providing community-based services that emphasize primary, secondary, and tertiary prevention"--Provided by publisher.